The neutral posture of the cervical spine is not unique in human subjects. (26th October 2018) - Newell, Robyn S.; Blouin, Jean-Sébastien; Street, John; Cripton, Peter A.; Siegmund, Gunter P.
Abstract: Cervical spine injuries often happen in dynamic environments (e.g., sports and motor vehicle crashes) where individuals may be moving their head and neck immediately prior to impact. This motion may reposition the cervical vertebrae in a way that is dissimilar to the upright resting posture that is often used as the initial position in cadaveric studies of catastrophic neck injury. Therefore our aim was to compare the "neutral" cervical alignment measured using fluoroscopy of 11 human subjects while resting in a neutral posture and as their neck passed through neutral during the four combinations of active flexion and extension movements in both an upright and inverted posture. Muscle activation patterns were also measured unilaterally using surface and indwelling electromyography in 8 muscles and then compared between the different conditions. Overall, the head posture, cervical spine alignment and muscle activation levels were significantly different while moving compared to resting upright. Compared to the resting upright condition, average head postures were 6–13° more extended, average vertebral angles varied from 11° more extended to 10° more flexed, and average muscle activation levels varied from unchanged to 10% MVC more active, although the exact differences varied with both direction of motion and orientation. These findings are important for ex vivo testing where the head and neck are statically positioned prior to impact – often in an upright neutral posture with negligible muscle forces – and suggest that current cadaveric head-first impact tests may not reflect many dynamic injury environments.